Encyclopedia of television - Newcomb, Horace; Museum of Broadcast Communications (New York : Fitzroy Dearborn, 2004)
Presents hundreds of alphabetized, cross-referenced articles on various aspects of television including series, networks, genres, actors, journalists, writers, and technology, covering the U.S. and Canada. This volume comprises S-Z.
v. 1. A-C -- v. 2. D-L -- v. 3. M-R -- v. 4. S-Z, Index.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Television broadcasting -- Encyclopedias; Télévision -- Encyclopédies.; TECHNOLOGY & ENGINEERING -- Television & Video; Television broadcasting; Televisie; encyclopedias; Encyclopedias; Encyclopedias; Encyclopédies.